Pulp involvement in deciduous teeth in pediatric patients under ten years of age - Saida Elizabeth Moreno García; Jaime Fernando Armijos Moreta; Silvia Marisol Gavilánez Villamarín (Universidad Médica Pinareña, 2023)
Introduction: Current dentistry prioritizes preventive measures as an effective way of reducing the main diseases that affect the oral cavity. Any alteration of the dentin-pulp complex, if not treated, can act as an irritant and trigger a pulp inflammatory process.